2016
DOI: 10.1021/acs.biochem.6b00038
|View full text |Cite
|
Sign up to set email alerts
|

The ssrA-Tag Facilitated Degradation of an Integral Membrane Protein

Abstract: ATP-dependent degradation plays a critical role in the quality control and recycling of proteins in cells. However, complete degradation of membrane proteins by ATP-dependent proteases in bacteria is not well-studied. We discovered that the degradation of a multidomain and multispan integral membrane protein AcrB could be facilitated by the introduction of a ssrA-tag at the C-terminus of the protein sequence and demonstrated that the cytoplasmic unfoldase-protease complex ClpXP was involved in the degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
(57 reference statements)
2
20
0
Order By: Relevance
“…We were the first to report that ClpXP could facilitate the degradation of an ssrA-tagged integral membrane protein AcrB. 14 We confirmed that the deletion of the clpX or clpP gene in E. coli strain hindered the degradation. AcrB-ssrA was membrane integrated before degradation, as confirmed by the reduction of efflux activity after the induced expression of ClpX in a clpX knockout strain.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…We were the first to report that ClpXP could facilitate the degradation of an ssrA-tagged integral membrane protein AcrB. 14 We confirmed that the deletion of the clpX or clpP gene in E. coli strain hindered the degradation. AcrB-ssrA was membrane integrated before degradation, as confirmed by the reduction of efflux activity after the induced expression of ClpX in a clpX knockout strain.…”
supporting
confidence: 56%
“…10−12 Before our discovery that ClpXP mediates the degradation of AcrB-ssrA, FtsH was the only protease that has been reported to completely degrade membrane integrated proteins. 13,14 FtsH is a protease anchored to the cytoplasmic side of the inner membrane. This protease has been shown to degrade several integral membrane proteins with a metastable structure.…”
mentioning
confidence: 99%
“…12 Challenging this assumption, however, a recent study showed that ClpXP degrades ssrA-tagged AcrB, an E. coli inner-membrane protein. 13 Here, we investigate a different ssrA-tagged integral membrane protein and find that its degradation requires FtsH but not ClpXP or ClpAP in vivo . Thus, which AAA+ protease degrades which ssrA-tagged inner-membrane protein depends on factors that are currently poorly defined.…”
mentioning
confidence: 97%
“…The cell culture was returned to the shaker, and aliquots of samples were withdrawn at the indicated time and analyzed. In a previous study, we found that the intensity of the radioactively labeled AcrB did not decrease over 24 hours [20]. Here we extended the experiment to 7 days (Figure 2A and 2B).…”
Section: Resultsmentioning
confidence: 55%